The Effect of Performance Allowance, Organizational Culture, and Work Discipline on Employee Performance at The Satuan Polisi Pamong Praja/Public Order Agency (SATPOL PP) of Yapen Serui Islands Regency- PAPUA - Siyani Siyani; Bonifasia Elita Bharanti; Agnes Puspitasari Sudarmo (Budapest International Research and Critics University, 2021)
This study aims to determine the effect of performance allowances, organizational culture, and work discipline on employee performance at the Public Order Agency (SATPOL PP) of Yapen Serui Islands Regency. This is a quantitative research with a causal approach. The research used a saturated sampling method by treating all research population, namely 82 SATPOL PP officers of the Yapen Serui Islands Regency, as the research sample. The data were analyzed using a descriptive analysis and multiple linear regression. The results showed that the performance allowance had a positive and significant effect on employee performance. In other words, the greater the performance allowance, the higher the employee’s performance. In contrast, organizational culture had no positive and insignificant effect on employee performance. The organizational culture applied at the SATPOL PP officers in the Yapen Serui Islands Regency did not significantly improve employee performance. Work discipline had a positive and significant effect on employee performance. The higher the employee’s work discipline, the higher their performance.